Codelivery of Paclitaxel and Parthenolide in Discoidal Bicelles for a Synergistic Anticancer Effect: Structure Matters. Issue 1 (20th November 2021) - Rad, Armin Tahmasbi; Hargrove, Derek; Daneshmandi, Leila; Ramsdell, Amanda; Lu, Xiuling; Nieh, Mu-Ping
Abstract : Nanotechnology has long been used to improve the tumor targeting of chemotherapeutics. The structure of these nanocarriers greatly affects their efficacy and toxicity. Herein, structurally stable nanodiscoidal phospholipid bicelles, which are capable of encapsulating anticancer drugs, paclitaxel (PTX) and parthenolide (PTL), are designed. This nanodiscoidal bicelle structure is shown previously to exhibit longer blood circulation, deeper tumor penetration, and increased tumor cell uptake compared with spherical particles of similar compositions. Structural characterization and loading capacity of the PTX‐ and PTL‐ loaded nanodiscs are conducted along with an investigation into the cytotoxicity of the bicelles based on the drug‐to‐lipid ratios of both drugs loaded separately and in combination. A significant synergistic effect between both loaded drugs is also observed in A549 lung cancer and drug‐resistant MDA‐MB‐231 cell lines. An in vivo study using mice bearing subcutaneous A549 tumors shows a long circulation time of the intravenously injected DiR‐loaded bicelles and significant antitumor efficacy of the PTX‐ and PTL‐loaded bicelles. This efficacious self‐assembled nanoparticle system displays great potential as a nanoplatform to codeliver multiple therapeutics or diagnostics for improving cancer therapy. Abstract : Nanomedicine made of a discoidal lipid bicelle, which contains cancer drug, Paclitaxel and NF‐κB pathway inhibitor, Parthenolide, shows significantly enhanced synergy for in vitro therapeutic efficacy and in vivo tumor targeting outcome through intravenous injection. The synergy also enhances the apoptotic efficacy on drug‐resistant cancer cells. Such a nanocarrier platform can also encapsulate a wide range of anticancer hydrophobic drugs.